Outcome of Breast Lump in Females attending Surgical Outpatient Department, Jinnah Hospital Lahore (Medical Forum Monthly, 2024)
Objective: Main focus of this research was to identify the consequence of breast lump in females attending surgical outpatient department, Jinnah Hospital Lahore.Study Design: Observational / descriptive / cross sectional study.Place and Duration of Study: that was conducted at the Outdoor of Surgical Units of Jinnah hospital, Lahore dated 15 April 2016 to 15 May 2016.Materials and Methods: All data was collected by patients through a feedback form that was prepared according to the knowledge of patients about breast diseases. Collected data analyses was made by SPSS version 13 and results was presented in different forms like tables, frequencies and percentages of variables Results: Total sample of 95 patients affected from breast lump taken. All the patients were divided into different age groups. 58 (61.05%) were age group between 16-35 years of age, 31 (32.63%) were between 36-55 years of age and 6(6.31%) patients were between the age group 56 years and above. In our study, 41 % patients had malignant carcinoma of the breast followed by fibroadenoma in 36% and breast accessible 15%.Most common age group suffering from carcinoma was 26-35 years of the age where it was found to be 13 (31.1%) Fibro adenoma was the most common disease of younger age group age 15-25 years of age.Conclusion: Conclusion of this study is the incidence of breast malignancy, fibro adenoma and inflammatory diseases is greater in our setup. However, there should be breast clinics screening programs so that breast cancer diagnosed at early stage. It is recommended now the surgeons managing patient’s age 30 years and above with breast lump should be vigillant and cautious so that early diagnosed and management of malignant breast lump should be carried out.